ANALISIS PENGARUH RASIO KEUANGAN DAN FAKTOR NON KEUANGAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris Pada Perusahaan Manufaktur di BEI tahun 2008-2010) - Ariffandita Nuri Muttaqin; Sudarno Sudarno (Diponegoro Journal of Accounting, 2012)
This research was aimed to analyze and to obtain empirical evidences on the relationship between financial ratios (liquidity, profitability, activity, leverage, sales growth, market value) and non financial factors (company size, public accountant reputation, previous audit report, auditor-client tenure,opinion shopping, audit lag) that affecting  auditor’s decision to give a going concern audit opinion. The population in this research is manufacturing companies listed at Indonesian stock exchange from 2008-2010, the sampling was conducted by purposive sampling method, by criteria of the samples are companies had negative net income after tax at least two period of financial statement. Collecting data was conducted by documentation and literature study wich is the data that used in this research is audited financial statements that published by manufacturing companies.audit client tenure The results indicate that profitabilty, market value, previous audit report, audit client tenure and opinion shopping are significantly affect the acceptence of going concern audit opinion. On the other hand, liquidity, activity, leverage, sales growth, companies size, public accountant reputation, audit lag does not have affect on the acceptence of going concern audit opinion.